The institutional framework of the new financial regulation model in the european union - Puente Regidor, Mónica (Nómadas. Critical Journal of Social and Juridical Sciences, 2017)
The economic crisis, which has been with us since 2008, has called into question the supervision and financial regulation model in the European Union (EU). The economic governing system, which was born after the creation of the European Economic and Monetary Union (EEMU), has been shown to be clearly insufficient in order to deal with the impact of the recession which has hit the twenty seven Member States of the EU. This situation has illustrated the need for a wider cooperation between the States, some supervisory institutions with a more systematic vision and a better designed and more specific financial system. The objective of this article is to analyze the modifications which have been made to the supervision model of the European financial system, the problems which have resulted and the lines of improvement which must be studied if the intention is that the supervision model of the European financial system is going to be a trustworthy, efficient and effective model in the future. To do this, the changes in the renovation of the financial supervision model in the EU, which have been made since 2011, will be studied. In the first place, the macro-prudential and microprudential supervision through the restructuring of the three fundamental bases of the financial system will be analyzed: banking system, market values and insurance. Secondly, a critique of the model will be carried out and the most problematic points of the system will be outlined in order to highlight areas which need improving and finally, the conclusions will be presented.